2018
DOI: 10.1126/science.aas8693
|View full text |Cite
|
Sign up to set email alerts
|

A hot and fast ultra-stripped supernova that likely formed a compact neutron star binary

Abstract: Compact neutron star binary systems are produced from binary massive stars through stellar evolution involving up to two supernova explosions. The final stages in the formation of these systems have not been directly observed. We report the discovery of iPTF 14gqr (SN 2014ft), a type Ic supernova with a fast-evolving light curve indicating an extremely low ejecta mass (≈0.2 solar masses) and low kinetic energy (≈2 × 1050ergs). Early photometry and spectroscopy reveal evidence of shock cooling of an extended he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 168 publications
10
117
0
Order By: Relevance
“…The mass of iron group ejecta falls between 0.01M and 0.04M . These values are compatible with the more modest explosion energies and nickel masses observed for hydrogen-rich low-mass progenitors (Pejcha & Prieto 2015) as well as for the ultra-stripped supernova candidates SN 2005ek (Drout et al 2013;Tauris et al 2013), SN 2010X (Kasliwal et al 2010;Moriya et al 2017) and iPTF 14gqr (De et al 2018). Thus, neutrino-driven explosion models do not appear to be underenergetic compared to observations in this mass range.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The mass of iron group ejecta falls between 0.01M and 0.04M . These values are compatible with the more modest explosion energies and nickel masses observed for hydrogen-rich low-mass progenitors (Pejcha & Prieto 2015) as well as for the ultra-stripped supernova candidates SN 2005ek (Drout et al 2013;Tauris et al 2013), SN 2010X (Kasliwal et al 2010;Moriya et al 2017) and iPTF 14gqr (De et al 2018). Thus, neutrino-driven explosion models do not appear to be underenergetic compared to observations in this mass range.…”
Section: Discussionsupporting
confidence: 81%
“…The existence of ultra-stripped supernovae was first suggested purely based on theoretical calculations of the final stages of mass transfer in close-orbit binaries (Tauris et al 2013) and it was realized that progenitors of neutron star gravitational wave mergers must have experienced such ultrastripped supernovae when the second-formed neutron star is born (Tauris et al 2013. A number of promising ultra-stripped supernova candidates have been identified based on observed properties of rapidly decaying supernova light curves (Drout et al 2013;Moriya et al 2017;De et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…USSNe are a proposed class linked to rapidly fading transients that are thought to be produced through the interaction of evolved massive stars, which have lost the majority of their envelopes via stripping by a neutron star in a close binary orbit (Tauris et al 2015). iPTF14gqr (De et al 2018), and perhaps SN 2010X (Moriya et al 2017), have been suggested to be members of this class. USSNe reach a V -band peak of approximately −16 mag, whilst LSQ13ddu is brighter by more than a factor of 100 at a peak of −19.7 mag.…”
Section: Light Curve Comparisonsmentioning
confidence: 99%
“…The He star is then expected to eventually undergo a SN explosion, which may either form a BNS that merges within a Hubble time, a BNS that is effectively stalled, an unbound BNS, or a NSBH system. The recent detection of a candidate ultra-stripped SN (De et al 2018) has provided additional strong evidence that HeNS binaries are the progenitors of BNSs (e.g., Dewi et al 2002;Ivanova et al 2003;Tauris et al 2013Tauris et al , 2015.…”
Section: Supernova Mass Loss Natal Kicks and Gravitational Radiationmentioning
confidence: 99%